Perancangan dan Pengembangan Sistem Pengendali Kelembaban Tanah Berbasis Arduino Uno untuk Tanaman Hias - Furqan, Aulia; Imilda; Iqbal, Taufiq (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to design and develop a soil moisture control system based on the Arduino Uno microcontroller for ornamental plants. The system uses a soil moisture sensor to detect moisture levels, which are then processed by the Arduino Uno to control a relay and water pump automatically. Soil moisture data is displayed on a 16x2 LCD with an I2C module, allowing real-time monitoring of soil conditions. During testing on different soil conditions (dry, moist, wet), the system successfully activated the water pump when moisture was low and turned it off when the soil was sufficiently moist. The use of I2C for the LCD helps reduce the number of pins used on the Arduino, improving system efficiency. The results show that the system can automatically maintain soil moisture, watering plants only when needed, thus preventing water wastage. This technology holds significant potential for use in ornamental plant care and can be further developed for agricultural applications. By implementing an automated system, the need for manual intervention is minimized, offering a more efficient solution for plant management.